AN OPEN LABEL PROSPECTIVE STUDY TO EXPLORE THE EFFICACY OF IPECACUANHA IN CASES OF BRONCHIAL ASTHMA- CASE REPORT - Dr. HITARTH MEHTA,; Dr. MUNJAL THAKAR, (The Bioscan, 2025)
Bronchial Asthma is a chronic inflammatory disorder characterized by episodes of breathlessness, wheezing, cough, chest tightness etc. caused due to bronchial hyper-responsiveness and variable air flow obstruction which is reversible spontaneously or with treatment. Homeopathic management of bronchial asthma shows promise as a complementary approach, particularly when integrated with conventional therapies. While preliminary evidence supports its potential benefits, further research is necessary to establish definitive clinical guidelines and validate the effectiveness of homeopathic treatments in asthma care. In India, about 15-20 million were estimated to be asthmatic. In India, its prevalence is about 2 percent. It is one of the causes of impaired quality of life with decreased ability to complete daily activities (85%), physical activity limitation (69%), loss in productivity at work (73%) or study (64%), and limits in leisure and lifestyle (78%). Homeopathy is a science based on laws of similar, which means it treats the disease with medicines producing similar symptoms when given in healthy individuals. Homeopathy treats the person as a whole. There are medicines given to treat the acute attacks of asthma as well as to prevent the recurrence of it, also to treat the allergies which may trigger the attack of asthma. KEYWORDS: Bronchial Asthma, Homoeopathy, Allergens, Ipecacuanha.